Accounting of environmental management and cost of health and hospital service in Metropolitan Lima - Choy Zevallos, Elsa Esther (2018)
Objective: To establish the need to have detailed and relevant environmental information, providing comprehensive information on the financial and social situation of the hospital centers, raising the hypothesis "The environmental management accounting provides relevant information that must be disclosed to achieve comprehensive information that hospital centers need to know about its financial situation and serve as a preventive and corrective instrument on environmental and social damage. Method: The study is qualitative and quantitative, of a descriptive and correlational level, non-experimental and with a cross-sectional design. Results: It is shown that there are hidden environmental costs that financial accounting does not reflect. Conclusion: We present the contribution of a structure of environmental accounts for health service processes.